Para além da heteronormatividade: uma análise dos eunucos representados por Estácio, Marcial e Suetônio (Roma, 80-121 d. C) - Ribeiro Junior, Benedito Inácio [UNESP] (2016)
The present work aims at assessing notions of gender, sex/sexuality and body in Roman Antiquity, through the analysis of the representations of the eunuchs’ bodies. To achieve this purpose, it was analysed a documentary corpus written between 80 and 121 d. C., composed of Epigrams, by Martial; the Silvae, by Statius; and the Life of Caesars, specifically Nero's biography, by Suetonius. Based on the theoretical approach of queer and gender studies, the present research analyses the bodily, sexual and identitary experiences of the castrated priests of Cybele - the galli -; of Earinus, an eunuch boy who kept affective and sexual relations with the Emperor Domitian and his wife; Sporus, an eunuch slave whom Nero ordered to castrate so that he could to take him as his wife. Through the methodological approach of critical discourse analysis, the sources were assessed in three dimensions: their modes of production, distribution and consumption; its aspects as literary texts and the aforementioned representations of the eunuchs. It was concluded from the study that, however different they could seem to be, the images constructed by the classical authors sought to create and maintain ideals of manhood and womanhood through the abjection and disqualification of the experiences of the eunuchs, using the dissent regarding their bodies to maintain masculinities and femininities under the Roman Principate. It is expected that the study will contribute with the destabilization of the memory crystallized by centuries of heteronormativity, by demonstrating that heterosexuality, as well as any other manifestation of sexualities, is not natural, but, in fact, historical, crossed by porosities and forged at the expense of exclusions, negotiations and oppressions.